PEER GROUP EDUCATION PREVENTION OF COVID-19 TRANSMISSION ON ADOLESCENTS IN SITOPENG CIREBON - Omay Rohmana; Ati Siti Rochayati (Jurnal Keperawatan Respati Yogyakarta, 2022)
Background: The positive number of Covid-19 in adolescents is second after adults. Adolescents have an over confident, feels strong, healthy, and faith that they will not be infected by covid 19 virus, in line with emotionally development, also difficult to receive parental advice, so they can be a virus carrier and potential increasing Covid-19 cases. Adolescents must be increased their consciousness. There must be match health education method in adolescents. Peer group methods can be considered. There are many studies on peer groups, however nothing related to healthy behavior prevention of covid-19 transmission yet. Aim: The aim of study is knowing the influence of peer group method in health education to adolescent healthy behavior prevention of covid-19 transmission. Methods: Research design is experiment pre-and post-intervention. The study population was all teenagers in Sitopeng Area, and the sample number was 15 peoples. Simple random sampling technique, and data analysis with paired t test. Results: The results show that peer group methods affect knowledge, attitudes, behavior using masks, and the habit of washing the hands of adolescents, but do not affect in distance behavior. Conclusion: peer education effective to increase adolescent awareness in health behavior prevention of covid-19 transmission.